2014
DOI: 10.1186/bf03351633
|View full text |Cite
|
Sign up to set email alerts
|

Geoelectric potential difference monitoring in southern Sumatra, Indonesia — Co-seismic change—

Abstract: Five geoelectric potential difference (electric field, here after) monitoring stations have been in operation since September 1997 in an area near Liwa town, southern Sumatra, Indonesia, to examine the relationship between electric field changes and earthquakes. Short-term electric field variations were found to correspond mainly to geomagnetic activity, while long-term variation was mostly gradual shift and was clearly correlated neither precipitation nor ground water level variations. Co-seismic electric fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 14 publications
(13 reference statements)
2
22
0
Order By: Relevance
“…Saroso, et al [9] also showed an anomaly during a series of Sumatran earthquakes through a transfer function analysis and a fractal analysis, which gives strong support to the above results. Mogi, et al [7] and Widarto, et al [8] also reported an anomalous earthquake precursor, using geoelectric and geomagnetic data with five cluster magnetotelluric in the Liwa segment at the southern part of the Sumatran fault system. Each reported that during the Bengkulu earthquake in 2000, the magnitude was mb > 4 with a moment magnitude of M w = 7.9 and a distance > 250 km from the Liwa cluster station.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saroso, et al [9] also showed an anomaly during a series of Sumatran earthquakes through a transfer function analysis and a fractal analysis, which gives strong support to the above results. Mogi, et al [7] and Widarto, et al [8] also reported an anomalous earthquake precursor, using geoelectric and geomagnetic data with five cluster magnetotelluric in the Liwa segment at the southern part of the Sumatran fault system. Each reported that during the Bengkulu earthquake in 2000, the magnitude was mb > 4 with a moment magnitude of M w = 7.9 and a distance > 250 km from the Liwa cluster station.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of Sumatran earthquake precursors, among others, [7][8][9], have analyzed the strong Sumatran earthquakes between 2004 and 2005. They studied the geomagnetic data on the ground-based station of Kototabang with the ground-based reference station of Biak (BIK, Papua Indonesia) as control.…”
Section: Introductionmentioning
confidence: 99%
“…Pride and Morgan, 1991;Gershenzon, 1992;Pride, 1994;Pride and Haartsen, 1996;Haartsen and Pride, 1997;Garambois and Dietrich, 2002;Huang, 2002;Ren et al, 2010a, b). Appearance of unambiguous electric field changes was mostly synchronized with the arrival of seismic wave (Yamada and Murakami, 1982;Honkura et al, 2000Mogi et al, 2000;Nagao et al, 2000;Matsushima et al, 2002;Ujihara et al, 2004). Recently we proposed a new mechanism for electric field generation by seismic wave or more specifically by ground motion, based on some observational examples (Honkura et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The orders of magnitude of these observed coseismic electric and magnetic signals are usually 1-100 mV km −1 and 0.01-1 nT (Ren et al, 2015). Coseismic electric signals during earthquakes of magnitude above 5 have been observed by Mogi et al (2000). Coseismic magnetic fields have been reported for the magnitude 6 Parkfield earthquake (Johnston et al, 2006), and for the magnitude 9.4 Sumatra earthquake (Guglielmi et al, 2006).…”
Section: Natural Earthquakesmentioning
confidence: 91%